A cidade das meninas e dos meninos : um estudo em representações sociais com crianças - Poubel, Paula Figueiredo (2021)
This study aims to understand and analyze the relationship between gender system and the construction of children's social knowledge about the city of Cuiabá. This was carried out within the Research Group on Child Psychology (GPPIN), in the Postgraduate Program in Education (PPGE / UFMT-Cuiabá). Inspired by the Sociology of Childhood, it understands children as social actors, with active participation in the process of building meaning on reality. It is theoretically based on the psychosocial approach based on the Theory of Social Representations (MOSCOVICI, 2003) and Cultural-Historical Theory (VIGOTSKI, 2009). And, from them, it dialogues with feminist epistemology; gender studies with a focus on the articulated discussion between gender system and Social Psychology (FLORES-PALACIOS, 2014); and feminist Geography (SPAIN, 1992; MASSEY, 2000). In this way, it delineates the data production process seeking the scientific visibility of childhood in the three moments described in the sequence: 1. Participant observation; 2. Production of city maps and individual interviews with girls and boys; 3. Construction of a maquette of the city by girls and boys, followed by a focus group. The data indicated that cultural artifacts and practices defined by adults seemed to communicate to children about the formation of two groups – boys and girls – reinforced through practices and activities that separate them in this way, for example, the queue of girls and the queue of the boy in the school environment. Based on objects, prescriptions, practices and gender identities spaces are divided (SPAIN, 1992) and designated as spaces for protection and relaxation for "calm girls" and spaces for adventure and leisure for "excited boys". Thus, the social representations about the city of Cuiabá have in common for the children the scale that starts from the families' houses, but they differ when girls expand the scale to commercial spaces that they usually attend with their mothers; and when boys make the difference in the parks and spaces where they are sometimes accompanied by their fathers. The data produced indicated that there is no social representation of a joint city supportting the thesis that there is a city for girls and a city for boys. The defense of a social identity of gender, feminine or masculine, shared by the social representations present in the culture in which the investigated children are inserted recommend the difference of social prescriptions and, consequently, of the spaces between genders. However, as produced by children in the face of mediation in the focus group, girls and boys re-elaborate the meanings and naturalization that exist in relation to such divisions and, faced with means that allows diversity and collaboration, create alternatives for the city. The potential of education in the construction of social knowledge that considers the creative activity of children, their rights as citizens and equal rights between genders stands out as a possible way to elaborate and build diversity in the possibilities of the city and experiences in the spaces for everyone.